Frequency of brushing and use of toothpaste with fluoride in children from 0 to 3 years ofage from the “Octavio Cordero” parish. Cuenca – Ecuador - Velásquez Cabrera, Leslye M. (2024)
Objectives: To determine toothbrushing frequency and the use of fluoride toothpaste in children aged 0 to 3 years in the ““Octavio Cordero”” parish. Materials and Methods: A quantitative, observational, descriptive, and cross- sectional study was conducted. Data was collected through a survey; a sample of 91 randomly selected children aged between 0 and 3 years was used. The SPSS software version 27 was employed to analyze the data, and the results were presented in frequencies and percentages. In addition, the relationship between variables was assessed using the Chi-square test with a significance of 0.05. Results: Forty-two point nine percent (42.9%) of the children brushed their teeth twice a day, and 33.0% used toothpastes containing 1000-1100 ppm fluoride. A significant relationship was found between the frequency of brushing and the age of the child (p<0.001); there is a significant relationship between the amount of fluoride used in toothpaste and the age of the infant (p<0.001); there was no relationship between the amount of paste applied to the toothbrush and the level of education of the parents (p=0.288). Conclusions: A higher frequency of toothbrushing was observed as age and the concentration of fluoride used in the toothpaste increased.